Morphological differentiation of catfishes of the family Ariidae occurring along the west coast of India - Kumar, Rajan; Jaiswar, Ashok Kumar; Chakraborty, Sushanta Kumar; Sarkar, Uttam Kumar; Lakra, Wazir Singh (Indian Journal of Fisheries, 2015)
Analysis of morphometric and meristic traits of twelve species of ariid catfishes occurring along the west coast of India indicated that these species can be differentiated based on morphological characteristics. Higher F-ratio for inter-nostril length, mouth width and adipose fin length signifies their role in species separation either alone or in combination with other morphometric characters. Stepwise discriminant function analysis (SDFA) included all considered variables showing their taxonomic significance with inter-nostril length, snout length and adipose fin length, as the most important discriminating characters. The first two discriminant functions accounted for the explanation of 89.44% of total variation. SDFA gives correct classification in 99.55% cases with only two misclassified cases among 447 specimens. Meristic features were found to be overlapping except in few instances and hence are less discriminating than morphometric variables.